2012
DOI: 10.1002/hyp.9553
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic model evaluation for large‐scale flood risk assessments

Abstract: 17For a nationwide flood risk assessment in Germany, simulations of inundation depth and 18 extent for all major catchments are required. Therefore, a fast two-dimensional hydraulic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
75
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 36 publications
(58 reference statements)
0
75
0
Order By: Relevance
“…Previous studies (e.g., [4,19]) demonstrated that choosing the lowest elevation for the route starting cells in the flat-water assumption is appropriate in flat areas. However, Falter et al [12] found a problem related to simplified flood models: isolated ponds were simulated by the infilling at the lowest point. This problem is likely to be less important in areas with a complex topography.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies (e.g., [4,19]) demonstrated that choosing the lowest elevation for the route starting cells in the flat-water assumption is appropriate in flat areas. However, Falter et al [12] found a problem related to simplified flood models: isolated ponds were simulated by the infilling at the lowest point. This problem is likely to be less important in areas with a complex topography.…”
Section: Resultsmentioning
confidence: 99%
“…This problem is likely to be less important in areas with a complex topography. Unfortunately, no studies (e.g., [4,12,19]) have provided the definition of a flat area. An additional problem is apparent.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The near-real-time application of hydrodynamic-numeric models is hampered by the need to provide appropriate estimates of initial and boundary conditions, to assimilate model simulations and observations (Matgen et al, 2007) and by considerable computational costs . Computation time depends particularly on the size of the computational domain and its spatial resolution (Falter et al, 2013) and the complexity level of model equations (Horritt and Bates, 2002). Alternatively, the inundated areas and inundation depths can be calculated in advance for a set of flood scenarios.…”
Section: State Of the Art And Related Workmentioning
confidence: 99%